(Dis)unity in Diversity: How Common Beliefs about Ethnicity Benefit the White Mauritian Elite*. Issue 4 (4th November 2015) - Salverda, Tijo
ABSTRACT: White Africans are particularly associated with the troubles South Africa and Zimbabwe have faced throughout their histories. The story of the Franco-Mauritians, the white elite of Mauritius, and how they have fared during more than forty years since the Indian Ocean island gained independence, is much less known. However, their case is relevant as a distinctive example when attempting to understand white Africans in postcolonial settings. Unlike whites elsewhere on the continent, Franco-Mauritians did not apply brute force in order to defend their position in the face of independence. Yet the society that emerged from the struggle over independence is one shaped by dominant beliefs about ethnicity. As this article shows, despite a number of inverse effects Franco-Mauritians have benefited from this unexpected twist, and part of the explanation for their ability to maintain their elite position lies therefore in the complex reality of ethnic diversity in postcolonial Mauritius.